2014
DOI: 10.1186/1757-1146-7-14
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high‐top and low‐top shoes on ankle inversion kinematics and muscle activation in landing on a tilted surface

Abstract: BackgroundThere is still uncertainty concerning the beneficial effects of shoe collar height for ankle sprain prevention and very few data are available in the literature regarding the effect of high-top and low-top shoes on muscle responses during landing. The purpose of this study was to quantify the effect of high-top and low-top shoes on ankle inversion kinematics and pre-landing EMG activation of ankle evertor muscles during landing on a tilted surface.MethodsThirteen physical education students landed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 52 publications
2
48
1
1
Order By: Relevance
“…8 The finding is also contrary to biomechanical studies that have shown increased levels of mechanical support in high cut shoes. 9,18,19,37,38 It does however support findings from Gottschalk & Pepple, 24 and Rovere et al 25 that high-cut shoes do not offer any advantage to low-cut shoes when protecting the ankle to excessive inversion. It is possible that the differences in results may relate to differences in task being performed and the size of the load being forced onto the ankle.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…8 The finding is also contrary to biomechanical studies that have shown increased levels of mechanical support in high cut shoes. 9,18,19,37,38 It does however support findings from Gottschalk & Pepple, 24 and Rovere et al 25 that high-cut shoes do not offer any advantage to low-cut shoes when protecting the ankle to excessive inversion. It is possible that the differences in results may relate to differences in task being performed and the size of the load being forced onto the ankle.…”
Section: Discussionmentioning
confidence: 65%
“…11,12,23 Further still, although the cut of the ankle is thought to be a risk factor for injury, there is still uncertainty concerning the beneficial effects of shoe collar height for ankle sprain prevention. 9 Gottschalk & Pepple, 24 found that high-cut shoes did not show greater prevention of ankle sprains compared to low-cut shoes especially for those who had no history of ankle sprains. Similarly, Rovere, Clarke, Yates and Burley 25 demonstrated that in comparison to low-cut basketball shoes, high-cut shoes were not more effective in reducing the incidence of ankle injury and further still fewest injuries were observed with low-cut shoes coupled with laced ankle stabilizers.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For EMG amplitude and frequency determination, raw signals were band-pass filtered at 10-500 Hz for EMG and then full-wave rectified [16]. For each of the entire 25 repetitions, the EMG amplitude (root mean square, EMG RMS ) was calculated over the middle third of each repetition based on a total range of motion of 90 • (a 30 • range of motion; 0.5 s for 60 • /s and 0.1 s for 300 • /s) during the concentric phase of the knee extension movement.…”
Section: Signal Processingmentioning
confidence: 99%